Aluminum alloy extrusion material manufacturing method and aluminum alloy extrusion material

By performing specific heat treatment and microstructure control on aluminum alloy ingots, an aluminum alloy extruded material with high tensile strength and elongation was prepared, which solved the problem of insufficient mechanical properties in the prior art and was suitable for the manufacture of high-strength structural materials.

JP2025019714APending Publication Date: 2025-02-07RESONAC CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023123471
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing aluminum alloy extruded materials have shortcomings in meeting tensile strength, 0.2% strength and elongation at the same time, making it difficult to produce products with sufficient mechanical properties.

Method used

By heating, extruding, quenching and artificial aging treatment of aluminum alloy ingots containing Si, Mg, Cu, Fe, Zr, Ti, to control the grain size and the formation of precipitation phases, aluminum alloy extruded materials with specific components and microstructures were prepared.

Benefits of technology

The high tensile strength, 0.2% strength and elongation of aluminum alloy extruded materials have been improved, and is suitable for the manufacture of high-strength structural materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025019714000001_ABST
    Figure 2025019714000001_ABST
Patent Text Reader

Abstract

To provide a method for manufacturing an aluminum alloy extrusion material exhibiting a high tensile strength, a 0.2% yield strength, and excellent elongation.SOLUTION: This aluminum alloy extrusion material manufacturing method comprises: a heating step of a billet made of a homogenized aluminum alloy containing Si, Mg, Cu, Fe, Zr, Ti and remaining Al at 460°C-560°C; an extrusion step of extruding the heated billet at the extrusion pressure of 15Mpa-30Mpa and the ram speed of 0.1 mm / sec-0.5 mm / sec to obtain an aluminum alloy extrusion material; and a die quenching step of cooling the obtained aluminum alloy extrusion material. The aluminum alloy extrusion material contains, by mass, Si:0.90%-2.00%, Mg:0.65%-0.90%, Cu:0.25%-0.50%, Fe:0.05%-0.50%, Zr:0.10%-0.25%, and Ti:0.010%-0.10%, and the remaining is Al and inevitable impurities.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an aluminum alloy extrusion product and an aluminum alloy extrusion product. [Background technology]

[0002] Aluminum alloys are lightweight and strong, and in recent years, their applications have expanded to transportation equipment such as automobiles and railway vehicles, civil engineering and construction fields, as well as household goods such as furniture and daily necessities, home appliances, etc. There is a demand for aluminum alloy materials to be further lightened by thinning, etc., and therefore there is a demand for further improvement in the strength of the material.

[0003] For example, Patent Document 1 discloses a method for producing an aluminum alloy extrusion material, which comprises extruding an aluminum-magnesium-silicon aluminum alloy extrusion material that contains magnesium, silicon, iron, titanium, copper, and manganese, with the balance being aluminum and unavoidable impurities, quenching the extrusion material by cooling, and performing natural aging and then artificial aging.

[0004] Patent Document 2 discloses a method for producing an aluminum alloy extrusion material having a chemical composition containing Si, Mg, Cu, Mn, Zr, Ti, Fe, V and Zn, with the balance being Al and unavoidable impurities, having a 0.2% yield strength of 350 MPa or more, a precipitate grain size of 5 μm or less, and an area ratio of fibrous structure in a cross section parallel to the hot extrusion direction of 95% or more.

[0005] Patent Document 3 discloses a method for producing an aluminum alloy extrusion material for cutting, which contains Si, Mg, Cu, Fe, Mn, and Cr, with the balance being Al and unavoidable impurities, and has a fibrous metal structure.

[0006] Patent Document 4 discloses an aluminum alloy extrusion material that contains Si, Mg, Cu, Fe, Mn, and Cr with the balance being Al and unavoidable impurities, in which, in a cross section perpendicular to the extrusion direction, crystal grains with an aspect ratio of 5.0 or less and a short-axis length of 50 μm or more and 1000 μm or less account for 90.0% or more of the area, and the electrical conductivity of the surface is 51.111ACS% or less. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2007-254809 A [Patent Document 2] JP 2014-074213 A [Patent Document 3] JP 2017-110238 A [Patent Document 4] International Publication No. 2022 / 264959 Summary of the Invention [Problem to be solved by the invention]

[0008] However, the aluminum alloy extrusion materials of Patent Documents 1 to 4 cannot simultaneously satisfy the requirements for tensile strength, 0.2% proof stress, and elongation, and therefore have a problem in that it is not possible to produce an aluminum alloy extrusion material with sufficient mechanical properties.

[0009] An object of one aspect of the present invention is to provide a method for producing an aluminum alloy extrusion product, which is capable of producing an aluminum alloy extrusion product excellent in tensile strength, 0.2% proof stress and elongation.

[0010] Another aspect of the present invention aims to provide an aluminum alloy extrusion material excellent in tensile strength, 0.2% yield strength and elongation. [Means for solving the problem]

[0011] The present invention has the following configuration. [1] A heating step of heating a billet made of a homogenized aluminum alloy containing Si, Mg, Cu, Fe, Zr, Ti and the balance Al to 460 ° C to 560 ° C; an extrusion step of extruding the heated billet at an extrusion pressure of 15 MPa to 30 MPa and a ram speed of 0.1 mm / sec to 0.5 mm / sec to obtain an aluminum alloy extrusion material; a die quenching step of cooling the aluminum alloy extrusion material obtained by the extrusion process; Including, The aluminum alloy extrusion material contains 0.90% by mass to 2.00% by mass of Si, 0.65% by mass to 0.90% by mass of Mg, 0.25% by mass to 0.50% by mass of Cu, 0.05% by mass to 0.50% by mass of Fe, 0.10% by mass to 0.25% by mass of Zr, 0.010% by mass to 0.10% by mass of Ti, and the remainder being Al and unavoidable impurities. [2] The method for producing an aluminum alloy extrusion material according to [1], wherein the die quenching step comprises cooling the aluminum alloy extrusion material with cooling water at 5°C to 40°C. [3] The method for producing an aluminum alloy extrusion material according to [1] or [2], further comprising an aging treatment step of subjecting the cooled aluminum alloy extrusion material to artificial aging treatment at 120°C to 240°C for 2 hours to 48 hours. [4] The method for producing an aluminum alloy extrusion material according to any one of [1] to [3], further comprising a homogenization treatment step of homogenizing the heated billet at 540°C to 580°C for 3 hours to 24 hours. [5] The method for producing an aluminum alloy extrusion material according to any one of [1] to [4], wherein the aluminum alloy extrusion material obtained by the extrusion process contains crystal grains of the aluminum alloy base material having a minor axis length of 50 μm to 100 μm in a cross section perpendicular to the extrusion direction. [6] The method for producing an aluminum alloy extrusion material according to any one of [1] to [5], wherein the heated billet has a dissolved Mg content of 0.003 mass % or more. [7] The method for producing an aluminum alloy extrusion material according to any one of [1] to [5], wherein the heated billet has a silicon solid solution content of 0.005 mass % or more. [8] The method for producing an aluminum alloy extrusion material according to any one of [1] to [7], wherein the aluminum alloy extrusion material contains 0.012 volume % to 0.030 volume % of β''-Mg2Si particles as precipitates. [9] The method for producing an aluminum alloy extrusion material according to [8], wherein the average particle size of the β''-Mg2Si particles is 2 nm to 8 nm.

[10] The density of the β''-Mg2Si particles in a cross section perpendicular to the extrusion direction is 2.0×10 22 pieces / m 3 ~6.0×10 23 pieces / m 3 The method for producing an aluminum alloy extrusion material according to [9].

[11] An aluminum alloy extrusion material, the aluminum alloy extrusion material is made of an aluminum alloy containing 0.90 mass% to 2.00 mass% Si, 0.65 mass% to 0.90 mass% Mg, 0.25 mass% to 0.50 mass% Cu, 0.05 mass% to 0.50 mass% Fe, 0.10 mass% to 0.25 mass% Zr, 0.010 mass% to 0.10 mass% Ti, with the balance being Al and unavoidable impurities; The aluminum alloy extrusion material includes crystal grains of an aluminum alloy base material having an aspect ratio of 5.0 or less and a length in a minor axis direction of 50 μm to 100 μm in a cross section perpendicular to the extrusion direction, The aluminum alloy extrusion material contains 0.012 volume % to 0.030 volume % of β''-Mg2Si particles as precipitates, the average particle size of the β''-Mg2Si particles is 2 nm to 8 nm; The density of the β''-Mg2Si particles in a cross section perpendicular to the extrusion direction is 2.0×10 22 pieces / m 3 ~6.0×10 23 pieces / m 3 Aluminum alloy extrusion material. Effect of the Invention

[0012] According to one embodiment of the method for producing an aluminum alloy extrusion material according to the present invention, an aluminum alloy extrusion material having excellent tensile strength, 0.2% proof stress and elongation can be produced.

[0013] One embodiment of the aluminum alloy extrusion material according to the present invention is excellent in tensile strength, 0.2% yield strength and elongation. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a perspective view showing an example of an extruded material according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of FIG. [Diagram 3] FIG. 2 is a diagram showing an example of a photograph of a polarized texture taken by an optical microscope in a cross section perpendicular to the extrusion direction of an aluminum alloy extrusion material according to an embodiment of the present invention. [Figure 4] 1 is a flowchart showing an example of a method for producing an aluminum alloy extrusion material according to an embodiment of the present invention. [Diagram 5] FIG. 1 is a perspective view showing an example of a burette. [Figure 6] FIG. 2 is a diagram showing an extrusion cross section (extrusion hole) of a die used in each of the Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, embodiments of the present invention will be described in detail. In this specification, unless otherwise specified, the numerical range indicated by "to" means that the numerical range includes the numerical range before and after the range as the lower limit and upper limit.

[0016] Before explaining the method for manufacturing an aluminum alloy extrusion material (which may also be referred to as an "extrusion material" in the following description) according to an embodiment of the present invention, the aluminum alloy extrusion material obtained by the method for manufacturing an aluminum alloy extrusion material according to this embodiment will be described.

[0017] <Aluminum alloy extrusion material> The extruded material according to this embodiment contains Si, Mg, Cu, Fe, Zr, and Ti with the balance being Al and unavoidable impurities, and contains aluminum alloy base material crystal grains having an aspect ratio of 5.0 or less and a minor axis length of 50 μm to 100 μm in a cross section perpendicular to the extrusion direction, and contains β''-Mg2Si particles as precipitates. The extruded material according to this embodiment can exhibit excellent tensile strength, 0.2% proof stress, and elongation by controlling the content, average grain size, and number density of the β''-Mg2Si particles in the cross section within predetermined ranges.

[0018] The tensile strength is a value obtained by dividing the maximum tensile force required until the extruded material breaks by the cross-sectional area of ​​the extruded material, and is also called tensile strength.

[0019] 0.2% proof stress is the stress at which the plastic (permanent) strain when the extrusion material is unloaded after being loaded with a strain is 0.2%. 0.2% proof stress is the magnitude of the load required to give a plastic (permanent) strain of 0.2%, and it means that even when this magnitude of load is applied and then unloaded, there is still 0.2% deformation. The higher the 0.2% proof stress, the stronger the extrusion material.

[0020] Elongation refers to the maximum value of permanent elongation at which an extruded material uniformly deforms when subjected to a tensile test, and is the permanent elongation of an extruded material after fracture based on JIS Z2241 expressed as a percentage of the original gauge length of the extruded material.

[0021] An example of the extruded material according to the present embodiment is shown in Fig. 1 and Fig. 2. Fig. 1 is a perspective view showing an example of the extruded material according to the present embodiment, and Fig. 2 is a cross-sectional view taken along line II of Fig. 1. As shown in Fig. 1 and Fig. 2, the extruded material 1 according to the present embodiment may have a hollow shape in which an inner partition wall 12 that divides the inside (hollow portion) into two is integrally formed with an outer peripheral wall 11 having a rectangular cross section. The extruded material 1 can be molded by extrusion molding or the like so as to have a hollow shape as shown in Fig. 1 and Fig. 2.

[0022] The thickness (cross-sectional thickness) of the outer peripheral wall 11 and the inner partition wall 12 of the extrusion material 1 is not particularly limited and can be set arbitrarily, but is preferably 4.5 mm to 6.5 mm. The thickness of the outer peripheral wall 11 and the inner partition wall 12 is more preferably 4.7 mm or more, and even more preferably 5.0 mm or more. Moreover, the thickness of the outer peripheral wall 11 and the inner partition wall 12 is more preferably 6.0 mm or less, and even more preferably 5.8 mm or less.

[0023] 1 and 2 use a three-dimensional orthogonal coordinate system with three axial directions (LT, L, and ST directions), with the width direction of the extruded material 1 defined as the LT direction, the length direction defined as the L direction, and the height direction defined as the ST direction, with the direction indicated by the arrow defined as the + direction and the opposite direction defined as one direction. The L direction is the extrusion direction when the extruded material 1 is molded. In Figs. 1 and 2, the +ST direction is defined as the top and the -ST direction is defined as the bottom, but this does not represent a universal top-bottom relationship.

[0024] [Components of aluminum alloy extrusions] As described above, the extruded material according to this embodiment contains Si, Mg, Cu, Fe, Zr, and Ti, with the balance being Al and inevitable impurities. The content of each element contained in the extruded material according to this embodiment will be described below.

[0025] (Si:0.90 mass%~2.00 mass%) The content of Si in the extruded material according to this embodiment is 0.90% by mass or more, and preferably 1.05% by mass or more. When the content of Si is 0.90% by mass or more, Si easily forms a compound by interaction with Mg, and when β''-Mg2Si precipitates are formed, this contributes to improving the strength of the extruded material. In addition, by adding an amount of Mg in excess of the amount added for generating β''-Mg2Si relative to the amount of Mg added later, the properties such as the strength of the extruded material after artificial aging treatment (aging treatment process described later) can be further improved. The content of Si may be 1.30% by mass or more, or 1.50% by mass or more.

[0026] The Si content in the extruded material is 2.00% by mass or less, and preferably 1.78% by mass or less. If the Si content is 2.00% by mass or less, grain boundary precipitation of simple Si can be suppressed, and the toughness of the extruded material can be further improved. In addition, the extrusion pressure can be reduced, and the productivity and yield can be improved. The Si content in the extruded material may be 1.50% by mass or less, or 1.25% by mass or less.

[0027] (Mg:0.65 mass%~0.90 mass%) The Mg content in the extruded material is 0.65% by mass or more, preferably 0.70% by mass or more, more preferably 0.72% by mass or more, and even more preferably 0.74% by mass or more. When the Mg content is 0.65% by mass or more, Mg easily forms a compound by interaction with Si, and when β''-Mg2Si precipitates are formed, it contributes to improving the strength of the extruded material. The Mg content in the extruded material is 0.90% by mass or less, preferably 0.88% by mass or less, and more preferably 0.83% by mass or less. When the Mg content is 0.90% by mass or less, the amount of precipitates can be kept within an appropriate range, improving the quenching sensitivity and suppressing an increase in pressure during extrusion. In addition, the generated β''-Mg2Si precipitates are easily dissolved at low temperatures, which further improves the accuracy of the shape of the product (extruded material).

[0028] (Cu:0.25 mass%~0.50 mass%) The Cu content in the extruded material is 0.25% by mass or more, preferably 0.28% by mass or more, more preferably 0.32% by mass or more, and even more preferably 0.36% by mass or more. If the Cu content is 0.25% by mass or more, the apparent amount of supersaturation of Mg2Si precipitates is increased, and the amount of β''-Mg2Si precipitates increases. This improves the age hardenability of the extruded material. In addition, compounds containing Cu are finely precipitated within the crystal grains, which contributes to improving the strength of the extruded material.

[0029] The Cu content in the extruded material is 0.50% by mass or less, preferably 0.45% by mass or less, and more preferably 0.42% by mass or less. If the Cu content is 0.50% by mass or less, the extrusion processability is improved and extrusion molding can be performed at a low extrusion pressure. In addition, the corrosion resistance of the extruded material is improved.

[0030] (Fe:0.05 mass%~0.50 mass%) The content of Fe in the extruded material is 0.050% by mass or more, preferably 0.080% by mass or more, more preferably 0.10% by mass or more, and even more preferably 0.13% by mass or more. If the content of Fe is 0.050% by mass or more, it combines with Al and Si to crystallize during casting, and can exert the effect of suppressing the coarsening of crystal grains. The content of Fe in the extruded material is 0.50% by mass or less, preferably 0.35% by mass or less, more preferably 0.30% by mass or less, and even more preferably 0.27% by mass or less. If the content of Fe is 0.50% by mass or less, it is possible to suppress the crystallization of needle-shaped Al-Fe-Si-based compounds, and further improve the extrusion moldability and toughness of the extruded product.

[0031] (Zr:0.10 mass%~0.25 mass%) Zr precipitates as Zr-containing fine particles (details will be described later) during homogenization, and becomes the nuclei of crystal grains (details will be described later) generated during extrusion processing. The Zr content in the extruded material is 0.10% by mass or more, preferably 0.11% by mass or more, and more preferably 0.13% by mass or more. If the Zr content is 0.10% by mass or more, the number of Zr-containing fine particles, i.e., the nuclei of recrystallization, is increased, and the coarsening of crystal grains (described later) can be suppressed. The Zr content in the extruded material is 0.25% by mass or less, preferably 0.20% by mass or less, and more preferably 0.17% by mass or less. If the Zr content is 0.25% by mass or less, the fluidity of the molten alloy is improved during casting, making it easier to form a material for extrusion by casting, and as a result, the productivity of the extruded material can be improved.

[0032] (Ti:0.010 mass%~0.10 mass%) Ti has the effect of refining crystal grains during casting, and also has the effect of suppressing ingot cracking during casting. The Ti content in the extruded material is 0.010% by mass or more, preferably 0.020% by mass or more, and more preferably 0.025% by mass or more. If the Ti content in the extruded material is 0.010% by mass or more, it can promote refinement of crystal grains during casting and suppress ingot cracking during casting. The Ti content in the extruded material is 0.10% by mass or less, preferably 0.085% by mass or less, and more preferably 0.060% by mass or less. If the Ti content is 0.010% by mass or more, the fluidity of the molten alloy is improved during casting, making it easier to form a material for extrusion by casting, and improving the productivity of the extruded material.

[0033] (Other elements) As inevitable impurities in the extruded material, for example, the contents of Mn and Cr are preferably as small as possible. If the contents of Mn and Cr as inevitable impurities are small, the quenching sensitivity of the extruded material is reduced, the effect of variations in the cooling rate on the strength of the extruded material is reduced, and the quality of the extruded material can be stabilized.

[0034] [Crystal grains of aluminum alloy base material] The crystal grains of the aluminum alloy base material included in the extruded material according to this embodiment have an aspect ratio of 5.0 or less and a short-axis length of 50 μm to 100 μm in a cross section perpendicular to the extrusion direction (hereinafter, sometimes simply referred to as a cross section). If the short-axis length is less than 50 μm, the short-axis length of the crystal grains of the aluminum alloy base material becomes too small, resulting in a decrease in strength of the extruded material. If the short-axis length exceeds 100 μm, the short-axis length of the crystal grains of the aluminum alloy base material becomes too large, resulting in a decrease in strength of the extruded material. The short-axis length is preferably 53 μm or more, more preferably 55 μm or more, and even more preferably 60 μm or more. The short-axis length is preferably 98 μm or less, more preferably 95 μm or less, and even more preferably 90 μm or less.

[0035] The length of the minor axis in the cross section of the crystal grain of the aluminum alloy base material refers to the average value of the lengths of the crystal grains of the aluminum alloy base material in the minor axis direction (average minor axis grain size). The average minor axis grain size is calculated by using commercially available image analysis software to calculate an image obtained by observing a cross section of the extruded material perpendicular to the extrusion direction, as described in the examples below.

[0036] The average minor axis grain size of the extruded material according to this embodiment is shown in Fig. 3, which is an example of a photo of a polarized texture taken by an optical microscope in a cross section perpendicular to the extrusion direction (Example 1 described later). As shown in Fig. 3, in a cross section perpendicular to the extrusion direction of the extruded material, the area ratio occupied by crystal grains of the aluminum alloy base material having an aspect ratio of 5.0 or less and a minor axis length of 50 μm to 100 μm is 90.0% or more, preferably 95.0% or more, and more preferably 98.0% or more. If the area ratio is 90.0% or more, cleavage fracture between crystal grains can be suppressed, and the strength of the extruded material against shear stress parallel to the extrusion direction can be improved.

[0037] The above area ratio is the average value measured in two visual fields in a range of 1.95 mm × 2.60 mm in a cross section perpendicular to the extrusion direction. Also, particles that are at the edge of the image and only partially visible are not included in the area of ​​each visual field or the area of ​​the crystal grains (i.e., the area of ​​each visual field used to calculate the area ratio is smaller than 1.95 mm × 2.60 mm). The area ratio of the crystal grains is the total area of ​​the two visual fields of the crystal grains that satisfy the above conditions, expressed as a percentage, relative to the total area of ​​the two visual fields.

[0038] [Volume fraction, average grain size, and number density of Mg2Si precipitates] In the manufacturing process of aluminum alloy extrusions, supersaturated Mg and Si dissolved in the aluminum alloy base material precipitate Mg2Si particles, which are a strengthening phase, or β''-Mg2Si particles, which are metastable precipitates of Mg2Si particles, in nano-order sizes, when heated by artificial aging.

[0039] When stress is applied to an aluminum alloy material containing these precipitates, the strength increases due to precipitation hardening, in which the particularly hard β''-Mg2Si particles suppress the movement of dislocations accompanying the plastic deformation of the aluminum alloy base material crystal grains. In order to fully achieve high strength through precipitation hardening, it is important to increase the volume fraction of β''-Mg2Si particles, to control the β''-Mg2Si particles within a predetermined size range that contributes to improving strength, and to disperse the β''-Mg2Si particles, i.e., to increase the number density of β''-Mg2Si particles.

[0040] Therefore, in this embodiment, the amount of Si and the amount of Mg in solid solution in the aluminum alloy base material before extrusion, the volume fraction of β''-Mg2Si particles in the aluminum alloy base material, the average particle size of β''-Mg2Si, and the number density of β''-Mg2Si are specified.

[0041] The amount of elemental solid solution in the alloy metal structure is the average value of the bulk of the alloy material. Methods for obtaining the amount of elemental solid solution in an alloy material include the electrical resistance measurement method, which calculates the amount of elemental solid solution in a metal structure from the relationship between the amount of elemental solid solution and electrical resistance, and the X-ray diffraction method, which calculates the amount of elemental solid solution from the lattice constant of a metal crystal, but these require pretreatment and analysis of the measurement sample, and require a large number of steps.

[0042] In addition, the average grain size of β''-Mg2Si can be obtained using a transmission electron microscope (TEM). However, TEM has limitations on the observation area, and quantifying fine precipitates of a few nm in size requires sampling a huge amount of material and TEM observation, which requires a large amount of labor.

[0043] Therefore, in this embodiment, the average grain size of β''-Mg2Si is calculated by theoretical calculation. Specifically, the amount of elemental solid solution and the phase fraction of precipitates calculated using a calculated equilibrium phase diagram based on the CALPHAD (CALculation of PHAse Diagrams, Computer Coupling of Phase Diagrams and Thermochemistry) method are used.

[0044] The CALPHAD method is a technique that uses a thermodynamic model to analyze various experimental data and theoretical calculation data, determine the Gibbs energy of each phase as a function of various state variables, and calculate the phase diagram using a computer.

[0045] In addition, when an element is dissolved in the aluminum alloy base material during extrusion and then a precipitate is precipitated by artificial precipitation, the state of the precipitate is predicted as follows. -Thermodynamic and kinetic data determined based on the CALPHAD method are used. The Langer-Schwartz theory and the Kampmann-Wagner method are used to calculate the particle size distribution of precipitates and to calculate the nucleation, growth, and coarsening of precipitates.

[0046] In a multi-component alloy consisting of n elements (n is an integer of 2 or more), spherical precipitates of matrix b phase are generated from supersaturated matrix a phase, and the precipitation of multiple precipitate phases is simulated simultaneously. In the LSKW method, the size of the precipitates is described by the following continuity equation, as shown in the following equation (1).

[0047]

number

[0048] where, in equation (1), f(r,t) is the size distribution of precipitates, j(r,t) is the nucleation rate, v is the velocity of the moving interface between the precipitates and the matrix phase, r is the radius of the precipitate, and t is time.

[0049] From the above equation (1), the average size, total number density, and volume fraction of the precipitates can be calculated, and further, the temperature and time changes of the precipitates as a function of time can be calculated.

[0050] In addition, based on the law of conservation of mass of an alloy system, the concentration of an element dissolved in the matrix phase (element solid solution amount), which changes due to the presence of m precipitates (m is an integer) associated with phase transformation and precipitation in the alloy, is calculated using the following formula (2).

[0051]

number

[0052] Here, in formula (2), c 0 i is the composition of element i, and c β i and c α i are the compositions of element i in the precipitate and matrix phase, respectively.

[0053] Based on the above-mentioned nucleation and growth model based on equation (1) and the model of element concentration changes accompanying growth based on equation (2), nucleation, growth and coarsening can be handled simultaneously.

[0054] Furthermore, the nucleation model of precipitates in a multi-component system uses the classical nucleation theory. The number of nucleation sites can be determined by experimental measurement, and the β''-Mg2Si of interest in this embodiment is calculated assuming that nucleation occurs in the bulk and that needle-like precipitates form.

[0055] In the precipitate growth kinetics model, it is assumed that local equilibrium conditions exist at the interface between the precipitate and the matrix phase, and that the chemical potential at the interface between the precipitate and the matrix phase changes only due to the Gibbs-Thomson effect with a constant molar volume.

[0056] From the above calculations, the volume fraction, average grain size, and number density of β''-Mg2Si can be calculated.

[0057] In the above calculation, the interface energy is used as an input for the parent phase growth and the precipitate growth. The precipitate formation site is assumed to be within the parent phase crystal lattice, and the precipitate morphology is assumed to be needle-like or plate-like.

[0058] By performing the simulation under the above conditions, appropriate calculations can be made taking into account the changes over time of precipitates in the aluminum alloy.

[0059] As described above, the extruded material according to this embodiment contains β″-Mg2Si particles as precipitates. The β″-Mg2Si particles have an average particle size of 2 nm to 8 nm and a number density of 2.0×10 22 pieces / m 3 ~6.0×10 23 pieces / m 3 and the volume fraction is 0.012 volume % to 0.030 volume %. The β″-Mg2Si particles have a size equal to or smaller than the crystal grain size of the aluminum alloy base material, and preferably precipitate in the FCC crystal lattice of the aluminum alloy base material.

[0060] Using the thermodynamic function model based on the above-mentioned thermodynamic calculations, the nucleation, growth, and coarsening processes of precipitates are obtained by numerical analysis based on the Langer-Schwartz theory and the Kampmann-Wagner method using kinetic data.

[0061] The volume fraction of β''-Mg2Si particles contained in the extruded material according to this embodiment is 0.012 volume% to 0.030 volume%. When the content of β''-Mg2Si particles is less than 0.012 volume% or more than 0.030 volume%, the strength of the extruded material against a shear stress parallel to the extrusion direction can be improved. The content of β''-Mg2Si particles is preferably 0.016 volume% or more, more preferably 0.017 volume% or more, and even more preferably 0.0175 volume% or more. The content of β''-Mg2Si particles is preferably 0.018 volume% or less, more preferably 0.020 volume% or less, and even more preferably 0.025 volume% or less.

[0062] The volume fraction of β''-Mg2Si particles is determined using the LSKW method described above.

[0063] The average particle size of the β''-Mg2Si particles is 2 nm to 8 nm. If the average particle size of the β''-Mg2Si particles is less than 2 nm or exceeds 8 nm, the strength of the extruded material against shear stress parallel to the extrusion direction decreases. The average particle size of the β''-Mg2Si particles is preferably 2.5 nm or more, more preferably 5 nm or more, and even more preferably 3 nm or more. The average particle size of the β''-Mg2Si particles is preferably 7 nm or less, more preferably 4 nm or less, and even more preferably 6 nm or less.

[0064] The average particle size of the β″-Mg2Si particles can be determined by the LSKW method described above.

[0065] The number density of β''-Mg2Si particles in the cross section perpendicular to the extrusion direction is 2.0×10 22 pieces / m 3 ~6.0×10 23 pieces / m 3 The number density of β''-Mg2Si particles is 2.0×10 22 pieces / m 3 Below 6.0×10, the contribution of particle dispersion strengthening by β''-Mg2Si particles in the aluminum alloy matrix is ​​small. 23 pieces / m 3 If the number density of β''-Mg2Si particles exceeds 3.0×10, the size of the β''-Mg2Si particles becomes large, and the contribution of the β''-Mg2Si particles in the aluminum alloy matrix to particle dispersion strengthening becomes small. In addition, the tensile strength and 0.2% yield strength of the extruded material decrease. 22 pieces / m 3 More than 4.0×10 is preferable. 22 pieces / m 3 More preferably, 8.0×10 22 pieces / m 3 More preferably, the number density of β''-Mg2Si particles is 5.0×10 23 pieces / m 3 Less than 3.0×10 is preferable. 23 pieces / m 3 Less than 1.0×10 is preferable.23 pieces / m 3 The following is even more preferred:

[0066] The number density of β''-Mg2Si particles is calculated using the LSKW method.

[0067] (Si particles) The extruded material according to the present embodiment may contain Si particles. The Si particles can be confirmed based on a quantitative analysis of the amount of each element in EDX (energy dispersive X-ray analysis) mapping of the same field of view as that used to calculate the area ratio of the crystal grains. Specifically, the Si particles are particles in which the Si content is 90 mass% or more in this analysis, with the remainder being Al. The Si particles may contain unavoidable impurities, or may be particles with 100 mass% Si (i.e., no remainder).

[0068] The average particle size of the Si particles may be 0.010 μm to 1.0 μm. The particle size of the Si particles can be determined based on a binarized image of the SEM image. The particle size of the Si particles is, for example, the circle-equivalent diameter of the black part of the binarized image (the diameter calculated from the area of ​​the circle when the black part is regarded as a circle).

[0069] The number of Si particles was measured using a SEM, for example, at a magnification of 10,000 times and a field of view of 12.1 μm×9.09 μm=109.989 μm 2 The total number of Si particles in the four fields of view is N Si The density of Si particles is calculated by dividing the number of particles by the area of ​​four fields of view (Si particle density [particles / mm 2 ]=((N Si [pieces]×10 6 ) / (4×109.989μm 2 )).

[0070] (Zr-containing fine particles) The extruded material according to the present embodiment may contain Zr-containing fine particles. By containing the Zr-containing fine particles, crystal grains are more easily formed with the Zr-containing fine particles as nuclei. The average particle size of the Zr-containing fine particles may be 0.010 μm to 1.0 μm. The particle size of the Si particles can be determined based on a binarized image of an SEM image. The particle size of the Si particles may be, for example, the circle equivalent diameter of the black part of the binarized image. In addition, when the binarized image does not have black and white inversion, the white part may be regarded as a circle to calculate the particle size of the Zr-containing fine particles. The Zr-containing fine particles may contain Si. The Zr-containing fine particles may be, for example, Al3Zr a S 1-a (O <a≦l)であってもよい。

[0071] The Zr-containing fine particles can be analyzed by observing the cross section of the extruded material and performing line analysis using EDX. For example, when the extruded material is subjected to line analysis using EDX, a Zr peak is observed at a position corresponding to the particle in the SEM photograph, and the particle that satisfies the above size condition is regarded as the Zr-containing fine particle. In the EDX line analysis, it is preferable that the peak intensity of Zr is the largest among elements other than Al. When the Zr-containing fine particles contain Si, it is preferable that the peak intensity of Zr is the largest among elements other than Al, or is the second largest after the peak intensity of Si.

[0072] The number of Zr-containing fine particles may be calculated using the same method as the above-mentioned method for calculating the number of Si particles.

[0073] [Tensile strength, 0.2% yield strength and elongation of aluminum alloy extrusions] The tensile strength of the extruded material according to this embodiment is 300 MPa to 330 MPa. The tensile strength is preferably 303 MPa or more, more preferably 305 MPa or more, and even more preferably 310 MPa or more. The tensile strength is preferably 328 MPa or less, more preferably 326 MPa or less, and even more preferably 320 MPa or less.

[0074] The tensile strength is a value measured by the method described in the Examples below (a value obtained using a No. 5 test piece (dimensions described below) in accordance with JIS Z2241).

[0075] The extruded material according to this embodiment has a 0.2% yield strength of 285 MPa to 300 MPa. The 0.2% yield strength is preferably 286 MPa or more, more preferably 289 MPa or more, and even more preferably 290 MPa or more. The 0.2% yield strength is preferably 298 MPa or less, more preferably 297 MPa or less, and even more preferably 296 MPa or less.

[0076] The 0.2% proof stress is a value measured by the method described in the Examples below (a value obtained using a No. 5 test piece (dimensions described below) according to JIS Z2241).

[0077] The extruded material according to this embodiment has an elongation (ductility) of 9% to 13%. The elongation is preferably 9.5% or more, more preferably 9.9% or more, and even more preferably 10.5% or more. The elongation is preferably 12.5% ​​or less, more preferably 12.0% or less, and even more preferably 11.8% or less.

[0078] The elongation is a value measured by a method conforming to JIS Z 2241. Specifically, the elongation is a value obtained by cutting a sample parallel to the rolling direction from the extruded material to prepare a test piece having a JIS No. 5 shape, and conducting a tensile test at room temperature.

[0079] The extruded material according to this embodiment contains 0.90% by mass to 2.00% by mass of Si, 0.65% by mass to 0.90% by mass of Mg, 0.25% by mass to 0.50% by mass of Cu, 0.05% by mass to 0.50% by mass of Fe, 0.10% by mass to 0.25% by mass of Zr, 0.010% by mass to 0.10% by mass of Ti, and the remainder being Al and unavoidable impurities. The extruded material according to this embodiment contains aluminum matrix crystal grains having a minor axis length of 50 μm to 100 μm in a cross section perpendicular to the extrusion direction, and contains 0.003% or more by mass of Mg solid solution and 0.005% or more by mass of Si solid solution before extrusion, and 0.012% by volume to 0.030% by volume of β″-Mg2Si particles as precipitates. In the extruded material according to the present embodiment, the average particle size of the β″-Mg2Si particles is set to 2 nm to 8 nm, and the density of the β″-Mg2Si particles in the above cross section is set to 2.0×10 22 pieces / m 3 ~6.0×10 23 pieces / m 3 As a result, the extruded material according to this embodiment can have a tensile strength of 300 MPa to 330 MPa, a 0.2% proof stress of 285 MPa to 300 MPa, and an elongation of 9% to 13%. Therefore, the extruded material according to this embodiment can have excellent tensile strength, 0.2% proof stress, and elongation.

[0080] <Method of manufacturing aluminum alloy extrusion material> A method for producing an aluminum alloy extrusion material according to this embodiment will be described. The method for producing an extrusion material according to this embodiment includes a melting step, a casting step, a homogenization step, a cooling step, a heating step, an extrusion step, a die quenching step, and an aging treatment step. The method for producing an extrusion material according to this embodiment does not need to include all of these steps. For example, the method for producing an extrusion material according to this embodiment does not need to include the melting step and the casting step if the cast material is available, and does not need to include each step up to the homogenization step if the homogenized material is available.

[0081] Fig. 4 is a flow chart showing an example of a method for producing an aluminum alloy extrusion material according to this embodiment. As shown in Fig. 4, first, a molten aluminum alloy is prepared (melting step: step S11).

[0082] The composition of the molten metal is preferably the same as the composition of the extruded material to be obtained. Since the elements contained in the extruded material are as described above, details are omitted.

[0083] Next, the molten metal obtained in the melting step (step S11) is cast to obtain a billet (extrusion material) (casting step: step S12).

[0084] The shape of the billet is not particularly limited as long as it can be formed into the shape of the pressed material. For example, the billet may be formed into a cylindrical shape as shown in FIG.

[0085] The casting method is not particularly limited, but examples thereof include vertical float continuous casting, vertical hot top continuous casting, and horizontal continuous casting.

[0086] Next, the billet obtained in the casting process (step S12) is subjected to a heat treatment to perform a homogenization process, in order to homogenize the metal structure of the billet and to sufficiently dissolve the atoms contained in the aluminum alloy, thereby obtaining a billet made of a homogenized aluminum alloy (homogenization process: step S13).

[0087] The homogenization step (step S13) can improve the strength of the billet.

[0088] The heat treatment temperature is preferably 540°C to 580°C. If the heat treatment temperature is 540°C or higher, the metal structure of the billet can be sufficiently homogenized, and the atoms contained in the aluminum alloy can be sufficiently dissolved. If the heat treatment temperature is 580°C or lower, melting of the intermetallic compound can be suppressed, so that coarsening of the particles of the intermetallic compound can be suppressed and the mechanical properties of the billet can be improved. The heat treatment temperature is more preferably 545°C or higher, and even more preferably 550°C or higher. The heat treatment temperature is more preferably 575°C or lower, and even more preferably 570°C or lower.

[0089] The heat treatment time is preferably 3 hours or more, more preferably 8 hours or more, and even more preferably 12 hours or more. If the heat treatment time is 3 hours or more, the metal structure of the billet can be sufficiently homogenized and the atoms contained in the aluminum alloy can be sufficiently solid-dissolved. The heat treatment time is preferably 24 hours or less, more preferably 20 hours or less, and even more preferably 18 hours or less. If the heat treatment time is 24 hours or less, coarsening of the particles of the intermetallic compound can be suppressed and the mechanical properties of the billet can be improved.

[0090] The liquidus temperature of the billet is preferably higher than the heat treatment temperature during homogenization. If the liquidus temperature of the billet is higher than the heat treatment temperature during homogenization, the generation of a liquid phase in the billet during homogenization can be suppressed, and the strength reduction of the extruded material cooled in the cooling step (step S14) can be reduced.

[0091] The liquidus temperature of the billet can be calculated, for example, by thermodynamic calculation using the CALPHAD method.

[0092] Next, the billet homogenized in the homogenizing step (step S13) is cooled (cooling step: step S14).

[0093] The temperature of the cooled billet is preferably 150° C. or less, and more preferably 100° C. or less. The billet may be cooled to 50° C. or less and stored.

[0094] The cooling method is not particularly limited, and water cooling, mist cooling, air cooling, fan cooling, natural cooling, etc. can be used.

[0095] The cooling rate is preferably 100° C. / hour or more, more preferably 200° C. / hour, and even more preferably 300° C. / hour.

[0096] Next, the billet cooled in the cooling step (step S14) is cut into a plurality of pieces (cutting step: step S15).

[0097] The cooled billet may be cut into a number of pieces, for example, at approximately equal intervals along the axial direction.

[0098] The method for cutting the billet is not particularly limited as long as it is possible to cut the billet, and any commonly used cutting method may be used.

[0099] Next, the cut billet is heated (heating step: step S16).

[0100] Heating the billet reduces the deformation resistance of the billet and maintains the components constituting the billet in a solid solution state.

[0101] The heating temperature is 460°C to 560°C. If the heating temperature is less than 460°C or exceeds 560°C, Mg and Si in the billet cannot be fully dissolved, and the strength of the resulting billet decreases. In addition, the solidus temperature of the aluminum alloy constituting the billet is easily exceeded, so that the intermetallic compounds in the aluminum alloy are easily melted and liquid is easily generated, and the strength of the resulting billet decreases. In addition, if the heating temperature is less than 460°C or exceeds 560°C, the deformation resistance of the billet increases and the extrusion pressure increases. Furthermore, in the extrusion step (step S17) described later, it becomes difficult to suppress the heating of the material due to the processing heat of the billet itself and the friction with the die. The heating temperature is preferably 470°C or higher, more preferably 475°C or higher, and even more preferably 480°C or higher. The heating temperature is preferably 540°C or lower, more preferably 535°C or lower, and even more preferably 525°C or lower.

[0102] The heated billet may contain both Mg and Si in solid solution.

[0103] The amount of dissolved Mg contained in the billet (solubility of Mg) is preferably 0.003% by mass or more. If the amount of dissolved Mg is 0.003% by mass or more, the amount of β''-Mg2Si particles precipitated in the extruded material is prevented from becoming insufficient, and the increase in crystal grains is prevented, so that a decrease in the strength of the extruded material can be prevented. The amount of dissolved Mg is more preferably 0.015% by mass, and further preferably 0.020% by mass or more.

[0104] The amount of dissolved Mg can be calculated by thermodynamic calculation using the CALPHAD method.

[0105] The amount of Si in solid solution contained in the billet (Si solid solution amount) is preferably 0.005% by mass or more. If the Si solid solution amount is 0.005% by mass or more, the amount of β''-Mg2Si particles precipitated in the extruded material is prevented from becoming insufficient, and the increase in crystal grains is prevented, so that a decrease in the strength of the extruded material can be prevented. The Si solid solution amount is more preferably 0.03% by mass or more, and further preferably 0.04% by mass or more.

[0106] The amount of dissolved Si can be calculated in the same manner as the amount of dissolved Mg.

[0107] Next, the billet heated in the heating step is extruded using an extrusion member such as a ram (push rod) to obtain an extruded material (extrusion step: step S17).

[0108] For example, the billet heated in the heating step (step S16) is loaded into a container and pressed against an extrusion die (hereinafter referred to as a die) having a predetermined opening shape using an extrusion member such as a ram (not shown), thereby obtaining an extruded material having a desired cross-sectional shape. In this embodiment, the extruded material preferably has a hollow shape as shown in FIG.

[0109] The extrusion speed is 15Mpa to 30Mpa. If the extrusion speed is less than 15Mpa or more than 30Mpa, the crystal grains in the extruded material tend to increase and the shape of the extruded material tends to deform, so that the strength of the extruded material tends to decrease. The extrusion speed is preferably 16Mpa or more, more preferably 20Mpa or more, and even more preferably 22Mpa or more. The extrusion speed is preferably 28Mpa or less, more preferably 27Mpa or less, and even more preferably 26Mpa or less.

[0110] The ram speed is 0.1 mm / sec to 0.5 mm / sec. If the ram speed is less than 0.1 mm / sec or more than 0.5 mm / sec, the crystal grains in the extruded material tend to increase and the shape of the extruded material tends to deform, so that the strength of the extruded material tends to decrease. The ram speed is preferably 0.2 mm / sec or more, and more preferably 0.3 mm / sec or more. The ram speed is preferably 0.4 mm / sec or less.

[0111] The extrusion speed is preferably 5.0 mm / min or more, and more preferably 6.5 mm / min or more. If the extrusion speed is 5.0 mm / min or more, strain is applied to the material, making it easier to form a metal structure having crystal grains, and the productivity of the extruded material is improved.

[0112] The extruded material obtained by the extrusion process contains crystal grains of the aluminum alloy base material having a length in the minor axis direction of 50 μm to 100 μm in a cross section perpendicular to the extrusion direction.

[0113] Next, the extruded material obtained in the extrusion process (step S17) is cooled to form a supersaturated solid solution (die-quenching process: step S17).

[0114] The cooling method is not particularly limited, but examples thereof include water cooling, mist cooling, fan cooling, and natural cooling.

[0115] When water cooling, mist cooling, or the like is used as the cooling method, cooling water can be used. The temperature of the cooling water is preferably 5°C to 40°C. If the temperature of the cooling water is 5°C to 40°C, the amount of precipitation of β''-Mg2Si particles in the extruded material is prevented from becoming insufficient, and the increase in crystal grains is prevented, and deformation of the shape of the extruded material is prevented, so that a decrease in strength of the extruded material can be prevented. The increase in crystal grains in the extruded material is prevented, and deformation of the shape of the extruded material is prevented, so that a decrease in strength of the extruded material can be prevented. The temperature of the cooling water is more preferably 10°C or higher, and even more preferably 14°C or higher. The temperature of the cooling water is more preferably 35°C or lower, and even more preferably 30°C or lower.

[0116] The cooling rate is 7.0°C / sec or more, preferably 10°C / sec or more, and more preferably 12°C / sec or more. If the cooling rate is 7.0°C / sec or more, precipitation of dissolved components is suppressed, making it easier to maintain a supersaturated solid solution, and improving the productivity of the extruded material. The cooling rate is 80°C / sec or less, preferably 40°C / sec or less, and more preferably 20°C / sec or less. If the cooling rate is 80°C / sec or less, deformation of the extruded material due to thermal contraction during cooling can be suppressed.

[0117] The target temperature is 150° C. or less, preferably 100° C. or less, and more preferably 50° C. or less. After the die quenching process (step S18), the extruded material may be stored at room temperature, for example, 30° C. or less, until the aging treatment process described later.

[0118] Next, the extruded material cooled in the die quenching step (step S18) is subjected to an artificial aging treatment (aging treatment step: step S19).

[0119] By subjecting the extruded material to artificial aging treatment, Mg2Si-based precipitates grow in the extruded material, and the strength of the extruded material can be improved.

[0120] The treatment temperature is 120°C or higher, preferably 140°C or higher, and more preferably 160°C or higher. If the treatment temperature is 120°C or higher, Mg2Si-based precipitates can be sufficiently precipitated in the extruded material. The treatment temperature is 240°C or lower, preferably 220°C or lower, and more preferably 200°C or lower. If the treatment temperature is 240°C or lower, excessive growth of Mg2Si-based precipitates in the extruded material can be suppressed, and the strength of the extruded material can be improved.

[0121] The treatment time is 2 hours or more, preferably 4 hours or more, and more preferably 5 hours or more. If the treatment time is 2 hours or more, Mg2Si-based precipitates can be sufficiently precipitated. The treatment time is 48 hours or less, preferably 16 hours or less, and more preferably 8 hours or less. If the treatment time is 48 hours or less, excessive growth of Mg2Si-based precipitates in the extruded material can be suppressed, and the strength of the extruded material can be improved, and the productivity of the extruded material can be improved.

[0122] The extruded material according to the present embodiment is manufactured by subjecting the extruded material to aging treatment.

[0123] As described above, the manufacturing method of the extruded material according to the present embodiment includes a heating step (step S16), an extrusion step (step S17), and a die quenching step (step S18). In the manufacturing method of the extruded material according to the present embodiment, in the heating step (step S16), the billet is heated to 450°C to 550°C, in the extrusion step (step S17), the heated billet is extruded at an extrusion pressure of 15 MPa to 30 MPa and a ram speed of 0.1 mm / sec to 0.5 mm / sec, and in the die quenching step (step S18), the extruded material obtained by the extrusion is cooled. As a result, the extruded material contains crystal grains having a minor axis length of 50 μm to 100 μm in a cross section perpendicular to the extrusion direction, and contains β″-Mg2Si particles at 0.012 vol % to 0.030 vol % as precipitates. The average particle size of the β''-Mg2Si particles is 2 nm to 8 nm, and the density of the β''-Mg2Si particles in the cross section perpendicular to the extrusion direction of the extruded material is 2.0 × 10 22 pieces / m 3 ~6.0×10 23 pieces / m 3 Therefore, the extruded material can have a tensile strength of 300 MPa to 330 MPa, a 0.2% proof stress of 285 MPa to 300 MPa, and an elongation of 9% to 13%. Therefore, the manufacturing method of the extruded material according to this embodiment can manufacture an extruded material excellent in tensile strength, 0.2% proof stress, and elongation.

[0124] The manufacturing method for the extruded material according to this embodiment includes a die quenching step (step S18), and thus the extruded material obtained by extrusion can be cooled with cooling water at 5°C to 40°C. This allows β''-Mg2Si particles to be sufficiently precipitated in the extruded material, suppresses excessive generation of precipitated particles, and suppresses deformation of the shape of the extruded material, thereby suppressing a decrease in strength of the extruded material. Therefore, the manufacturing method for the extruded material according to this embodiment can exhibit the tensile strength and 0.2% proof stress of the extruded material, and can improve the elongation.

[0125] The manufacturing method for the extruded material according to this embodiment includes an aging treatment step (step S19), and thus the cooled extruded material can be artificially aged at 120°C to 240°C for 2 hours to 48 hours. This allows the β''-Mg2Si particles precipitated in the extruded material to grow, improving the strength of the extruded material. Therefore, the manufacturing method for the extruded material according to this embodiment can improve the tensile strength and 0.2% proof stress of the extruded material.

[0126] The manufacturing method for the extruded material according to this embodiment includes a homogenization treatment step (step S13), and thus the heated billet can be homogenized at 540°C to 580°C for 3 hours to 24 hours. This makes it possible to obtain a billet made of a homogenized aluminum alloy. Therefore, the manufacturing method for the extruded material according to this embodiment can reliably exhibit the tensile strength, 0.2% proof stress, and elongation of the extruded material.

[0127] In the manufacturing method of the extruded material according to the present embodiment, in the extrusion step (step S17), the extruded material obtained by the extrusion process can contain crystal grains having a minor axis length of 50 μm to 100 μm in a cross section perpendicular to the extrusion direction. This can increase the strength of the extruded material. Therefore, the manufacturing method of the extruded material according to the present embodiment can improve the tensile strength and 0.2% proof stress of the extruded material.

[0128] In the manufacturing method of the extruded material according to this embodiment, the amount of Mg dissolved in the heated billet can be set to 0.003 mass% or more in the heating step (step S16). This allows sufficient precipitation in the β''-Mg2Si particles in the extruded material, and allows the precipitate particles to exist in the extruded material in a finely dispersed state in the FCC crystal lattice of the aluminum alloy matrix, thereby increasing the strength of the extruded material. Therefore, the manufacturing method of the extruded material according to this embodiment can improve the tensile strength and 0.2% proof stress of the extruded material.

[0129] In the manufacturing method of the extruded material according to this embodiment, the amount of Si dissolved in the heated billet can be set to 0.005 mass% or more in the heating step (step S16). This allows sufficient precipitation of β''-Mg2Si particles in the extruded material, and allows the crystal grains to exist in the extruded material in a small state, thereby increasing the strength of the extruded material. Therefore, the manufacturing method of the extruded material according to this embodiment can improve the tensile strength and 0.2% proof stress of the extruded material.

[0130] The manufacturing method for the extruded material according to the present embodiment can include 0.03 volume % to 0.050 volume % of β''-Mg2Si particles as precipitates contained in the extruded material. This increases the strength of the extruded material. Therefore, the manufacturing method for the extruded material according to the present embodiment can improve the tensile strength and 0.2% proof stress of the extruded material.

[0131] The manufacturing method for the extruded material according to this embodiment can set the average particle size of the β''-Mg2Si particles contained in the extruded material to 2 nm to 8 nm. This increases the strength of the extruded material. Therefore, the manufacturing method for the extruded material according to this embodiment can improve the tensile strength and 0.2% proof stress of the extruded material.

[0132] In the method for producing an extruded material according to the present embodiment, the density of β″-Mg2Si particles in a cross section perpendicular to the extrusion direction is set to 2.0×10 22 pieces / m 3 ~6.0×10 23 pieces / m 3 This increases the strength of the extruded material. Therefore, the method for producing an extruded material according to this embodiment can improve the tensile strength and 0.2% yield strength of the extruded material.

[0133] According to the manufacturing method of the extruded material of this embodiment, it is possible to manufacture an aluminum alloy extruded material having excellent tensile strength, 0.2% proof stress and elongation, and therefore the method can be effectively used for manufacturing, for example, high-strength structural materials.

[0134] As described above, the embodiment has been described, but the above embodiment is presented as an example, and the present invention is not limited to the above embodiment. The above embodiment can be implemented in various other forms, and various combinations, omissions, substitutions, modifications, etc. can be made without departing from the gist of the invention. These embodiments and their modifications are included in the scope and gist of the invention, and are included in the scope of the invention and its equivalents described in the claims. EXAMPLES

[0135] The following examples are provided to further explain the embodiments, but the embodiments are not limited to these examples. Examples 1 to 14 are working examples, and Examples 15 to 37 are comparative examples. Each example in the table is indicated with "No."

[0136] <Example 1 to Example 37> [Production of aluminum alloy extrusions] (Forging and homogenization) A billet having a circular cross section with a diameter of 156 mm was produced by continuous casting using an aluminum alloy consisting of the elements, Al, and unavoidable impurities shown in Table 1. The obtained billet was subjected to a homogenization treatment for 14 hours at the temperature shown in Table 2. Thereafter, the billet was cooled to 30°C at 180°C / sec. Next, the cooled billet was heated to 500°C. Note that in Tables 1 and 2, the parts shown with a gray background are parts that deviate from the gist of this embodiment.

[0137] (Extrusion processing) The billet was then heated to the temperature shown in Table 2 and extruded using a die.

[0138] Figure 6 shows the extrusion cross section (extrusion hole) of the die used in each of the Examples and Comparative Examples. A billet was extruded using the die D1 shown in Figure 6 to form the extrusion material 1 shown in Figures 1 and 2. The extrusion material 1 has a hollow shape in which an outer peripheral wall 11 having a rectangular cross section is integrally formed with a middle partition wall 12 that divides the inside (hollow portion) into two.

[0139] The die D1 shown in Fig. 6 has an extrusion hole D10 having an outer peripheral wall forming hole D11 for forming the outer peripheral wall 11 of the extrusion material 1 and a middle partition wall forming hole D12 for forming the middle partition wall 12. In the die D1, the outer peripheral wall forming hole D11 had a horizontal dimension L1 of 50 mm and a vertical dimension L2 of 50 mm. The width T1 of the outer peripheral wall forming hole D11 and the middle partition wall 12 was 2.5 mm, the inner radius of curvature Ri of the outer peripheral wall forming hole D11 was 2.5 mm, and the outer radius of curvature Ro was 5 mm.

[0140] In each of the Examples and Comparative Examples, extrusion processing was performed with an 8-inch direct extruder using the die D1 in Figure 6. The extrusion pressure and ram speed in this extrusion process in each of the Examples and Comparative Examples are shown in Table 2.

[0141] The liquidus temperature of the billet, the amount of dissolved Mg before extrusion, and the amount of dissolved Si before extrusion were calculated. The calculation results of the liquidus temperature, the amount of dissolved Mg before extrusion, and the amount of dissolved Si before extrusion are shown in Table 2.

[0142] ((liquid phase temperature of billet)) The liquidus temperature of the billet was calculated by the CALPHAD method.

[0143] ((Solution amount of magnesium before billet extrusion)) The amount of dissolved Mg in the billet before extrusion was calculated using the CALPHAD method.

[0144] ((Solution amount of Si before billet extrusion)) The amount of dissolved Si in the billet before extrusion was calculated using the CALPHAD method.

[0145] (Die quench and ageing) Immediately after the extrusion step, a die quenching step was performed, and the temperature of the extruded material was set to 30° C. The cooling water temperatures used for cooling in the die quenching step in each Example and Comparative Example are shown in Table 1. The extruded material after the die quenching step was subjected to artificial aging treatment (aging treatment) at 180° C. for 3 hours to obtain an aluminum alloy extruded material.

[0146] [Various measurements of aluminum alloys] The extrusion cross-section thickness and average minor axis grain size of the aluminum alloy extrusion material were measured to evaluate the extrudability of the aluminum alloy extrusion material. The results are shown in Table 3.

[0147] (Extrusion cross-sectional thickness of aluminum alloy extrusion material) For the obtained aluminum alloy extrusion material, the wall thickness in a cross section perpendicular to the extrusion direction was measured using a micrometer at positions 2 cm apart and at positions 5 cm apart.

[0148] (Average minor axis grain size of crystal grains) A test piece was cut out from the part (side wall) having a thickness in the LT direction to a thickness of L: 10 mm, ST: 10 mm, and LT: 2 mm (the L-ST surface was cut off by 0.5 mm to make the thickness 2 mm). This test piece was embedded in resin, and the cross section perpendicular to the L direction was mirror-finished by buffing, and then etched with Barker's electrolyte. The image of the deflected texture in the processed cross section taken by an optical microscope was analyzed as follows using the image processing software ImageJ. The observation range was 1.95 mm x 2.60 mm, and the number of images was two in each example and each comparative example. An example of a photograph for observing crystal grains is shown in FIG. 3. In each image, the proportion of crystal grains with an aspect ratio of 5.0 or less and a short axis length of 50 μm to 100 μm was calculated. Note that particles at the edge of the image and partially outside the image are not calculated in either the field area or the area of ​​the crystal grains. The area ratio of the crystal grains is the percentage of the total area of ​​the two visual fields of the crystal grains that satisfy the above condition with respect to the total area of ​​the two visual fields.

[0149] (Extrusion properties of aluminum alloy extrusions) The extrusion shape of the aluminum alloy extrusion material was observed, and the extrudability in the above extrusion process was evaluated based on the following criteria. ((judgment criteria)) A: The extrusion pressure is less than 25 MPa, and the extruded material has no fractures or visible cracks. B: The extrusion pressure is 25 MPa or more, the extruded material has cracks, or there are visible cracks in the extruded material. At least one of the above.

[0150] (Mechanical properties of aluminum alloy extrusions) As the mechanical properties of the aluminum alloy extrusion material, the tensile strength, 0.2% yield strength and elongation were measured. The measurement results are shown in Table 4.

[0151] (Tensile strength, 0.2% yield strength and elongation of aluminum alloy extrusions) From the aluminum alloy extrusion material obtained in each Example and Comparative Example, No. 5 test pieces specified in JIS Z2241 were taken, and tensile tests were performed in the manner of JIS Z2241 to measure tensile strength, 0.2% proof stress, and elongation (total elongation). Specifically, the test pieces were cut out along the extrusion direction (L direction) with a gauge length of 50 mm, a parallel length of 60 mm, a width of 25 mm, a thickness of 2 mm, and a shoulder R of 30 mm. The tensile strength was calculated by performing a tensile test (in accordance with JIS Z2241) at room temperature (24°C) at a crosshead speed of 2 mm / min, and the 0.2% proof stress and elongation were measured by the offset method. When the tensile strength was 300 MPa to 330 MPa, it was determined that the extrusion material had a tensile strength appropriate for the extrusion material. When the 0.2% proof stress was 285 MPa to 300 MPa, it was determined that the extrusion material had a 0.2% proof stress appropriate for the extrusion material. It was determined that an elongation of 9% to 13% was appropriate for an extruded material.

[0152] [Various measurements of β''-Mg2Si particles] Table 4 shows the volume percentage, average particle size, and number density of β''-Mg2Si particles, which are precipitates in the aluminum alloy extrusion material.

[0153] (Volume %, average particle size and number density of β''-Mg2Si particles) Calculations were made using the LSKW method.

[0154] [Table 1]

[0155] [Table 2]

[0156] [Table 3]

[0157] [Table 4]

[0158] As can be seen from Tables 1 to 4, the tensile strength, 0.2% yield strength and elongation of the aluminum alloy extrusions in each of the Examples were all high, whereas at least one of the tensile strength, 0.2% yield strength and elongation of the aluminum alloy extrusions in each of the Comparative Examples was low.

[0159] Therefore, if a billet made of homogenized aluminum alloy is heated to 460°C to 560°C in the heating process, and then the heated billet is extruded at an extrusion pressure of 15 MPa to 30 MPa and a ram speed of 0.1 mm / sec to 0.5 mm / sec in the extrusion process, and then cooled with cooling water at 5°C to 40°C to produce an aluminum alloy extrusion material, it can be said that an aluminum alloy extrusion material having excellent tensile strength, 0.2% proof stress and elongation can be produced. [Explanation of symbols]

[0160] 1. Aluminum alloy extrusions

Claims

1. A heating step of heating a billet made of a homogenized aluminum alloy containing Si, Mg, Cu, Fe, Zr, Ti, and a balance of Al, to 460°C to 560°C; an extrusion step of extruding the heated billet at an extrusion pressure of 15 MPa to 30 MPa and a ram speed of 0.1 mm / sec to 0.5 mm / sec to obtain an aluminum alloy extrusion material; a die quenching step of cooling the aluminum alloy extrusion material obtained by the extrusion process; Including, The aluminum alloy extrusion material contains 0.90 mass% to 2.00 mass% Si, 0.65 mass% to 0.90 mass% Mg, 0.25 mass% to 0.50 mass% Cu, 0.05 mass% to 0.50 mass% Fe, 0.10 mass% to 0.25 mass% Zr, 0.010 mass% to 0.10 mass% Ti, and the remainder being Al and unavoidable impurities.

2. 2. The method for producing an aluminum alloy extrusion material according to claim 1, wherein the die quenching step comprises cooling the aluminum alloy extrusion material with cooling water at 5°C to 40°C.

3. 2. The method for producing an aluminum alloy extrusion material according to claim 1, further comprising an aging treatment step of subjecting the cooled aluminum alloy extrusion material to artificial aging treatment at 120°C to 240°C for 2 hours to 48 hours.

4. 2. The method for producing an aluminum alloy extrusion material according to claim 1, further comprising a homogenization treatment step of homogenizing the heated billet at 540°C to 580°C for 3 hours to 24 hours.

5. 2. The method for producing an aluminum alloy extrusion material according to claim 1, wherein the aluminum alloy extrusion material obtained by the extrusion process contains crystal grains of the aluminum alloy base material having a minor axis length of 50 μm to 100 μm in a cross section perpendicular to the extrusion direction.

6. 2. The method for producing an aluminum alloy extrusion material according to claim 1, wherein the amount of dissolved Mg in the heated billet is 0.003 mass % or more.

7. 2. The method for producing an aluminum alloy extrusion material according to claim 1, wherein the amount of silicon dissolved in the heated billet is 0.005 mass % or more.

8. The aluminum alloy extrusion material contains β''-Mg as precipitates. 2 The method for producing an aluminum alloy extrusion material according to claim 1, wherein the aluminum alloy extrusion material contains 0.012 volume % to 0.030 volume % of Si particles.

9. The β''-Mg 2 The method for producing an aluminum alloy extrusion material according to claim 8, wherein the average particle size of the Si particles is 2 nm to 8 nm.

10. In a cross section perpendicular to the extrusion direction, 2 The density of the Si particles is 2.0×10 22 pieces / m 3 ~6.0 x 10 23 pieces / m 3 The method for producing an aluminum alloy extrusion material according to claim 9,

11. An aluminum alloy extrusion material, the aluminum alloy extrusion material is made of an aluminum alloy containing 0.90% by mass to 2.00% by mass of Si, 0.65% by mass to 0.90% by mass of Mg, 0.25% by mass to 0.50% by mass of Cu, 0.05% by mass to 0.50% by mass of Fe, 0.10% by mass to 0.25% by mass of Zr, 0.010% by mass to 0.10% by mass of Ti, and the remainder being Al and unavoidable impurities; The aluminum alloy extrusion material includes crystal grains of an aluminum alloy base material having an aspect ratio of 5.0 or less and a length in a minor axis direction of 50 μm to 100 μm in a cross section perpendicular to the extrusion direction, The aluminum alloy extrusion material contains β''-Mg as precipitates. 2 Contains 0.012 vol % to 0.030 vol % Si particles; The β''-Mg 2 The average particle size of the Si particles is 2 nm to 8 nm; In a cross section perpendicular to the extrusion direction, 2 The density of the Si particles is 2.0×10 22 pieces / m 3 ~6.0 x 10 23 pieces / m 3 Aluminum alloy extrusion material.

Citation Information

Patent Citations

  • Aluminum alloy extruded shape material having excellent impact absorbing property and satisfactory hardenability, and its production method

    JP2007254809A

  • High strength aluminum alloy extruded material and method of producing the same

    JP2014074213A

  • Aluminum alloy extrusion material for cutting work excellent in fatigue strength property and manufacturing method therefor

    JP2017110238A

  • Aluminum alloy extrusion and method for manufacturing same

    WO2022264959A1